HELMINTH PARASITES OF THE SUBDESERT TOAD, AMIETOPHRYNUS (BUFO) XEROS (ANURA: BUFONIDAE) - Sulieman, Yassir; Afifi, Azzam; Awad, Higazi M.; Pengsakul, Theerakamol (International Journal of Research -GRANTHAALAYAH, 2015)
Sixty-nine subdesert toads, Amietophrynus (Bufo) xeros, were collected in Shendi, Sudan, from August to November 2014, and examined for the first time for the presence of internal helminth parasites. Sixty-seven (97.1%) of the toads were found infected with one or more helminth species including, four Nematoda: Aplectanamacintoshii, Rhabdiasbufonis, Strongyloidesprokopici, and Oswaldocruzia sp.; one Trematoda: Mesocoelium sp.; one Cestoda: Lanfrediella sp. A higher prevalence and intensity of infection was found in male toads compared with females, and old toads were found to harbor a higher prevalence and intensity of infection when compared to younger ones. However, neither of these differences was statistically significant. In addition, there were no significant correlations found between the gender of the toads examined and either the prevalence or intensity of infection of any of the helminth species. Likewise, the prevalence and intensity of infection of the helminth species were not significantly correlated with the snout-vent length of the toads.